Chronic lymphocytic leukemia: a disease of activated monoclonal B cells - Damle, Rajendra N. (2010)
B-cell type chronic lymphocytic leukemia (CLL) has long been considered a disease of resting lymphocytes. However cell surface and intracellular phenotypes suggest that most CLL cells are activated cells, although only a small subset progresses beyond the G1 stage of the cell cycle. In addition, traditional teaching says that CLL cells divide rarely, and therefore the buildup of leukemic cells is due to an inherent defect in cell death. However, in vivo labeling of CLL cells indicates a much more active rate of cell birth than originally estimated, suggesting that CLL is a dynamic disease. Here we review the observations that have led to these altered views of the activation state and proliferative capacities of CLL cells and also provide our interpretation of these observations in light of their potential impact on patients.